Detection of Aflatoxin M1, Heavy metals (As, Pb, Hg, Cd, Al) and Polychlorinated biphenyls in demineralized whey powder produced from sweet whey - Takalloo, Iman; Sani, Ali Mohamadi (Asian Journal of Biological and Life Sciences, 2015)
In this study, aflatoxin M1 (AFM1), heavy metals (As, Pb, Hg, Cd, Al) and polychlorinated biphenyls (PCBs), were evaluated in 90% demineralized whey powder (DWP-90), produced from sweet whey. For this purpose, 12 DWP-90 samples (400g/package) collected during 6 months. AFM1 was found in 100% of the samples. The average, maximum and minimum amounts (45.7, 11 and 99ppt respectively) were less than maximum level (1000ppt) according to Iranian national standard. AFM1 content was less than maximum limit according to Codex and EC standards for milk (50ppt). The average concentrations of Pb, Cd, As, Hg, Al and PCBs were 18, 1, <20, 10, 2679 and <6 ppb respectively (less than maximum limits in Codex and EC standards, except for Hg and Al). Heavy metals and PCBs content in DWP-90 compared with natural mineral waters in Codex. So PCBs and AFM1 were not a safety risk in DWP-90.
Keywords: Aflatoxin M1; Demineralized whey powder; Heavy metals; Polychlorinated biphenyls